Evaluation of Retinal and Choroidal Thickness in Fuchs’ Uveitis Syndrome - Ozlem Balci; Mustafa Ozsutcu (Journal of Ophthalmology)
Purpose. We aimed to investigate retinal and choroidal thickness in the eyes of patients with Fuchs’ uveitis syndrome (FUS). Methods. Fifteen patients with unilateral FUS and 20 healthy control subjects were enrolled. Spectral domain optical coherence tomography (Spectralis HRA+OCT, 870 nm; Heidelberg Engineering, Heidelberg, Germany) was used to obtain retinal and choroidal thickness measurements. The retinal nerve fiber layer (RNFL) thickness, macular thickness, and choroidal thickness of the eyes with FUS were compared with the unaffected eye and the eyes of healthy control subjects. Results. The mean choroidal thickness at fovea and at each point within the horizontal nasal and temporal quadrants at 500 μm intervals to a distance of 1500 µm from the foveal center was significantly thinner in the affected eye of FUS patients compared with the unaffected eye of FUS patients or the eyes of healthy control subjects. However, there were no significant differences in RNFL or macular thickness between groups. Conclusions. Affected eyes in patients with FUS tend to have thinner choroids as compared to eyes of unaffected fellow eyes and healthy individuals, which might be a result of the chronic inflammation associated with the disease.